INTERPRETASI BAWAH PERMUKAAN SISTEM PANAS BUMI DIWAK DAN DEREKAN BERDASARKAN DATA GRAVITASI - Syamsul Ilmi; Udi Harmoko; Sugeng Widada (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
ABSTRACTResearch has been carried out using a gravity method that aims to interpret the subsurface structure of the Diwak - Derekan hot springs area based on the Bouguer anomaly data. It also aims to investigate the geothermal system in the area. The data aquisition was taken using gravitymeter Lacoste & Romberg.Data processing had been done with high correction tool, tidal correction, drift correction, gravity absolute correction, gravity theoretical correction, free air correction, Bouguer correction, terrain correction to get the complete Bouguer anomaly. Bouguer anomolay is projected to flat plane and upward continuation is used to separate the regional and residual anomaly. For 2D modelling interpretation by Grav2DC software.The results of study showed the complete Bouguer anomaly contour pair of positive and negative contour indicate a fault zone below the surface. Interpretation is strengthened by the results of the modeling showed a fault of Diwak - Derekan areas trending southwest- northeast. This fault zone is used as a media outlet fluid to the surface of geothermal systems.Keywords: Gravity Method, 2D modelling, Diwak, Derekan